Ultrafine particulate matter and high-level benzene urban air pollution in relation to oxidative DNA damage - AVOGBE, PATRICE HODONOU; Ayi-Fanou, Lucie; Autrup, Herman; Loft, Steffen; Fayomi, Benjamin; SANNI, AMBALIOU (My University, 2005)
Air pollution, containing high-level of ultrafine particles (UFP) and benzene, is a prominent environmental health problem in many cities of the World. We investigated the level of oxidative DNA damage in mononuclear blood cells (MNBC) by the comet assay as DNA strand breaks (SB) and formamidopyrimidine DNA glycosylase (FPG) sensi- tive sites in residents from three urban locations in Cotonou, Benin (taxi-moto drivers, subjects living near roads with intense traffic and suburban residents) and rural residents. Exposure was characterized by urinary excretion of S-phenylmercapturic acid (S-PMA), a bio- marker of benzene exposure, and by ambient UFP. There were clear stepwise gradients with respect to ambient UFP, S-PMA excretion and oxidative DNA damage with rural subjects 5 suburban subjects 5 residents living near highly trafficed roads 5 taxi-moto drivers. Polymorphisms in glutathione peroxidase (GPX), NAD(P)H:quinone oxido- reductase 1 (NQO1) and glutathione S-transferase (GST) genes were assessed for effect modification. Subjects with GSTT1 null genotype had lower urinary S-PMA excretion than subjects carrying the plus genotype. Urinary S-PMA excretion correlated with SB (R 1⁄4 0.17) and FPG sites (R 1⁄4 0.25) in MNBC. The correlation between S-PMA and SB was strongest in subjects with NQO1 1/ 2 and 2/ 2 genotypes (R 1⁄4 0.37), and between S-PMA and FPG sensitive sites in subjects with the GSTP1 B/ B genotype (R 1⁄4 0.39). In conclusion, this study shows that urban air with high levels of benzene and UFP is associated with elevated levels of SB and FPG sites in MNBC, and that NQO1 and GST genes may modulate the effect.
Keywords: Air pollution; formamidopyrimidine DNA glycosylase; GPX; glutathione peroxidase; benzene; PAHs; S-phenylmercapturic acid